2016
DOI: 10.1111/1440-1681.12563
|View full text |Cite
|
Sign up to set email alerts
|

PAK1‐cofilin phosphorylation mediates human lung adenocarcinoma cells migration induced by apelin‐13

Abstract: Adipocytokines apelin peptide, the ligand of APJ (putative receptor related to the angiotensin receptor AT1), plays key roles in the pathogenesis and deterioration of cancer. In lung cancer, apelin elevating microvessel densities has been reported. Our previous research has characterized that apelin-13 promoted lung adenocarcinoma cell proliferation. However, the effect of apelin on metastasis in lung adenocarcinoma and the underlying mechanisms remain unclear. This study shows that apelin-13 induced human ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Apelin expression in tumors is regulated by hypoxia [181] and is suggested to promote tumor growth in several ways. Apelin directly stimulates tumor cell proliferation [181][182][183], tumor cell migration and metastasis [184,185]. Apelin also stimulates neoangiogenesis and microvascular proliferation within the tumor, leading to enhanced tumor growth [174,176,186,187].…”
Section: Apelin/aplnr Pathwaymentioning
confidence: 99%
“…Apelin expression in tumors is regulated by hypoxia [181] and is suggested to promote tumor growth in several ways. Apelin directly stimulates tumor cell proliferation [181][182][183], tumor cell migration and metastasis [184,185]. Apelin also stimulates neoangiogenesis and microvascular proliferation within the tumor, leading to enhanced tumor growth [174,176,186,187].…”
Section: Apelin/aplnr Pathwaymentioning
confidence: 99%
“…In the cardiovascular system, apelin/APJ can reduce blood pressure, promote the formation of new blood vessels, and reduce arterial tension and the heart preload (Yu et al, ). In addition, apelin/APJ can regulate GI function and insulin sensitivity, promote cell proliferation and migration, induce angiogenesis, maintain cardiovascular homeostasis, regulate immune function, and even protect retinal neuronal cells (Adam et al, ; Castan‐Laurell et al, ; Chun et al, ; Ishimaru et al, ; Kostopoulos, Spiroglou, Varakis, Apostolakis, & Papadaki, ; D. Lv et al, ; Tiani et al, ; G. Wang et al, ; Q. Zhou, Cao, & Chen, ). Much research has shown that apelin may play a role in body fluid homeostasis, including water and food consumption, as well as energy metabolism (Cao, Li, & Chen, ; L. Guo et al, ; Najafipour, Soltani Hekmat, Nekooian, & Esmaeili‐Mahani, ; Taheri et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the cardiovascular system, apelin/APJ system can reduce blood pressure, promote the formation of new blood vessels, reduce arterial tension, and the heart preload (Yu et al, ). In addition, apelin/APJ system can regulate gastrointestinal function and insulin sensitivity, promote cell proliferation and migration, induce angiogenesis, and regulate immune function (Adam et al, ; Castan‐Laurell et al, ; Lv et al, ; Tiani et al, ; Wang et al, ; Zhou, Cao, & Chen, ). Various researches show that apelin may play a role in body fluid homeostasis (Najafipour, Soltani Hekmat, Nekooian, & Esmaeili‐Mahani, ).…”
Section: Introductionmentioning
confidence: 99%